Role of trace amine-associated receptor 1 in nicotine's behavioral and neurochemical effects. (November 2018) - Liu, Jian-Feng; Seaman, Robert; Siemian, Justin; Bhimani, Rohan; Johnson, Bernard; Zhang, Yanan; Zhu, Qing; Hoener, Marius; Park, Jinwoo; Dietz, David; Li, Jun-Xu
Abstract Nicotine addiction and abuse remains a global health issue. To date, the fundamental neurobiological mechanism of nicotine addiction remains incompletely understood. Trace amine-associated receptor 1 (TAAR1) is thought to directly modulate dopaminergic system and are thought to be a neural substrate underlying addictive-like behaviors. We aimed to investigate the role of TAAR1 in nicotine addictive-like behaviors. TAAR1 expression after nicotine treatment was evaluated by western blotting. c-Fos immunofluorescence and in vivo fast-scan cyclic voltammetry were used to examine the activation of brain regions and dopamine release, respectively. We then thoroughly and systematically examined the role of TAAR1 in mediating nicotine-induced sensitization, nicotine discrimination, nicotine self-administration, nicotine demand curve, and the reinstatement of nicotine-seeking. Local pharmacological manipulation was conducted to determine the role of TAAR1 in the nucleus accumbens (NAcs) in the reinstatement of nicotine-seeking. We found that the expression of TAAR1 protein was selectively downregulated in the NAc, with no change in either dorsal striatum or prefrontal cortex. TAAR1 activation was sufficient to block nicotine-induced c-Fos expression in the NAc, while also reducing nicotine-induced dopamine release in the NAc. Systemic administration of TAAR1 agonists attenuated the expression and development of nicotine-induced sensitization, nicotine self-administration, the reinstatement of nicotine-seeking, and increased the elasticity of nicotine demand curve, while intra-NAc infusions of a TAAR1 agonist was sufficient to attenuate nicotine reinstatement. Moreover, TAAR1-knockout rats showed augmented cue-induced and drug-induced reinstatement of nicotine-seeking. These results indicated that modulation of TAAR1 activity regulates nicotine addictive-like behaviors and TAAR1 represents a novel target towards the treatment of nicotine addiction.